Implementasi Undang-Undang Nomor 14 Tahun 2008 Tentang Keterbukaan Informasi Publik di DPRD Kabupaten Sidoarjo - Dini Purnawansyah; Yuni Lestari (JKMP (Jurnal Kebijakan dan Manajemen Publik), 2014)
The purposes of this research where to find phenomena in local legislators related with implementation Law number 14 of 2008 that is concerning Public Information Transparency and to detect the supporting and inhibiting factors. The location of this research was local legislators office in Sidoarjo Regency. Research methods used descriptive qualitative. This method is used to collect data and information through interview, observation, and documentation. While, data analysis were data description, data analysis, and conclusions. The results of this research showed that local legislators Sidoarjo Regency weren’t optimal yet in implementing of this Law. It can be measured by interview results can be concluded that the information that must be provided and published on a regular basis then the information must be provided every times, was still had not available yet with completely and accurately. And the media public information existence have available information completely, it had not sufficiently yet representative to contain public information that should be accessible by public quickly and easily.